Enhancement of Bachelor of Science Nursing Program for military veterans through an Academic Practice Partnership. - McNeil, Sandra Oliver; Benkert, Ramona; Lauzon Clabo, Laurie M. (Journal of Professional Nursing, 2020)
• Military veterans have unique healthcare needs. • Educating military veterans as nurses can address the need to increase diversity in the nursing workforce. • Veteran Affairs Medical Centers can provide a unique clinical experiences for military veteran nursing students.